Jo. Adamvs Kvlmvs, Uratislaviensis Physicus Dantisc Med. et Phys. Prof. P. Acad. Imp. Natur. Cur. et Societ. Reg. Scient. Berolin. Sodalis. / J. Houbraken. - Houbraken, Jacobus (1698-1782) (Janssonius Van Waesberge, 1743)
Przedstawia portret w popiersiu Johanna Adamusa Kulmusa.